Application of Weather Modification Technology for Wetting Peatlands as a Mitigation Measure for Forest and Land Fires in South Kalimantan Province - Fitriano, Lutfi; Poniman, Aris; Harsono, Gentio (Formosa Journal of Science and Technology, 2024)
Weather Modification Operation (WMO) was conducted in South Kalimantan Province from July 29 to August 9, 2024, to support the wetting of peatland as a measure to mitigate forest and land fires. (karhutla). This operation was carried out by inserting superfine powder NaCl seeding material, which was sown into the clouds using the TNI AU's Casa 212-200 aircraft. Global and local weather factors were taken into account in determining the timing and location of seeding. El Niño and Indian Ocean Dipole (IOD) factors that were in the neutral phase as well as warm sea surface temperatures (+0.5°C to +2.0°C) around the waters of South Kalimantan contributed to the success of this operation. In the implementation of OMC, analysis of air humidity in the 925 to 500 mb layer showed the potential for convective cloud growth in most of the target areas, although humidity decreased on several days in certain layers. The implementation of the operation successfully increased rainfall in the target area, with rain intensity varying between 0 to 40 mm per day during the OMC period, resulting in significant wetting of peatland and an increase in groundwater table height (TMAT) at critical locations. The contribution of OMC successfully reduced the risk of forest and land fires by decreasing the number of hotspots in the priority peatland areas of South Kalimantan. In line with the Indonesian government's climate change mitigation strategy, we expect the long-term impact of this activity to reduce the intensity of forest and land fires and carbon emissions from peatlands in this area.